How can Artificial Intelligence help e-commerce firms to improve customer satisfaction and business performance. - Du, Zhonghui (2017)
The purpose of this paper is to study how can Artificial Intelligence help e-commerce firms to improve customer satisfaction and business performance by analyzing the literature, questionnaire and examples. There are three key concepts in this paper: e-commerce, customer satisfaction and AI technology, and the entire research focuses on these three concepts. In order to deeply realize the applications of AI in e-commerce, this paper firstly presents the evidences and screenshots of AI applications that we have seen in the daily life. Then questionnaire has been conducted to study the level of customer satisfaction to multiple applications of AI techniques in e-commerce. Finally, this paper helps to find out the potential value-added activates or points through analyzing the customer value chain and value creation chain, and customers’ expectations for AI development in e-commerce field. Going through the entire dissertation, it can be concluded that AI technology used in e-commerce has brought both direct and indirect impacts on the customer satisfaction and AI technology is playing a vital role in improving business performance.